Factors Affecting the Purchase of Staple Goods: An Empirical Study of Edible Oil Purchase in Tripura - Das, Manish (Indian Journal of Marketing, 2013)
Edible oil is the most important type of cooking medium in India and Tripura is no exception. The present paper is an attempt to find out the underlying factors that are actively considered by the consumers in Tripura while purchasing edible oil. The paper also seeks to find out whether there is any significant difference in the selection of the underlying factors by the husband and the wife of the same family. The paper concludes that Visible Brand, Healthy Brand, Brand Communication, Packaging Design, Price of the Oil, and Taste of the oil were the most important underlying factors considered by the consumers while purchasing edible oil. This paper also concludes that there is no significant difference among the selection of variables while purchasing edible oil by the husband and the wife of the same family.